The Autowarning Telltale: A New Safety Monitoring Device for Pillar Extraction Operations - David Bigby (International Conference on Ground Control in Mining, 2011)
Room and pillar mining with full pillar extraction is one of the most hazardous systems of underground coal mining, a significant hazard being the potential for sudden goaf override. The Autowarning Telltale (AWTT) is a new development for pillar extraction operations, based on the well proven and simple Rockbolting Telltale safety monitoring device. It is now being applied in room and pillar coal mines in India, with significant potential for application worldwide. The Autowarning Telltale is an intrinsically safe low-cost, self-contained unit installed into the roof either during pillar development or prior to pillar extraction. It provides a highly visible warning via flashing Light Emitting Diodes (LEDs) when a preset level of roof movement has been exceeded. The paper provides a full description of the instrument and two case histories of its initial application at fully-mechanized Indian sites using the split and fender technique.